The phenomenon of singleness from the perspective of islamic religious education an analytical study of rowo kandangan village - Nur Laila; Anas Rodin; Junedi; Nayatul Dwi Fariska; Waliyah; Muhammad Alwan Farih; Husna Nashihin (At Turots: Jurnal Pendidikan Islam, 2023)
The background of this research is based on the high rate of single people in Rowo Village with a population of 2,939 people, with details of 1,497 married, 35 divorced, 131 divorced and finally unmarried totaling 1,222 people, for those who are single numbering 10 people. Despite having quite good Natural Resources but the rate of singleness is quite high. Therefore, through this research aims to explore the phenomenon of singleness from the perspective of Islamic religious education in Rowo Kandangan Village. This study uses a phenomenological approach to understand the experience and meaning of the phenomenon of singleness from an Islamic religious education perspective. The type of research used is field research because it was conducted directly at the location where the subjects were located. The method used was qualitative, with data collection techniques through observation, interviews, and documentation. Data sources consisted of primary data from community leaders, religious leaders, and the surrounding community, while secondary data came from books and journals. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. To ensure data validity, two triangulation methods were used: sources and techniques. The results of the study show thatThe phenomenon of being single or fear of marriage does occur among the people of Rowo Kandangan Village, especially those aged 40 years and above, although the term being single is not yet widely known by the community, but symptoms and attitudes that lead to fear of marriage have appeared in the social life of the community, the factors that cause someone to experience being single are economic instability, domestic violence in the surrounding environment, trauma in the past, high criteria in determining a partner and focus on career,These factors give rise to feelings of worry, doubt, and even rejection of the institution of marriage. In perspective Islamic religious education marriage is a religious command that is highly recommended because marriage is the longest worship in life and in it there are great blessings and rewards, so that offspring continue, however the practice of being single or tabattul withThe reason for fear is without any basis in Islamic law and is not in accordance with the guidance of the Prophet Muhammad SAW and has resulted in a decline in public health, a reduction in offspring or regeneration and an increasing number of single people in Rowo village.The novelty element of this research explores the phenomenon of singleness from the perspective of Islamic religious education.